Project-Based Learning and Writing Skill: Are They Related for Junior High School Students? - Siti Fatimah (PGRI Provinsi Jawa Timur, 2022)
Integrating students’ knowledge, attitude, and abilities, Project-Based Learning (PjBL) allows for the creation of a productive and pleasurable learning environment. The goal of implementing PjBL is to provide students with a fun learning environment in which they can also practice and enhance their English. Writing is an important ability to have in English class. The purpose of this research was to examine how PjBL influenced the compositional competence of 9th graders at SMP Negeri 44 in Surabaya. In this work, we utilized a pre-experimental design. Forty students from Grade IX-A were used in the study, with one student from the experimental group serving as a representative. When compared to the .05. threshold for statistical significance, the results showed that the Sig. value of (Sig. (2-tailed)) was .001. It was decided that the alternative hypothesis (Ha) should be “accepted”, whereas the null hypothesis (Ho) should be “rejected”. Subsequently, it was calculated that the post-test group had a mean of 85.5, which was considerably higher than the 72.6 mean of the pre-test group. PjBL has been found to successfully enhance students' writing skills. If educators are incentivized to use PjBL to introduce the idea of pedagogical approach in the classroom, students' academic performance may increase. Therefore, it is proposed that other researchers conduct comparable studies using PjBL with different methods and English skills, such as critical thinking.